INFLUENCE OF GENERAL EDUCATORS’ KNOWLEDGE ON TEACHING PERFORMANCE FOR STUDENTS WITH LEARNING DIFFICULTIES IN INTERMEDIATE SCHOOLS IN RIYADH, SAUDI ARABIA - Reem Alshuwaysh; Loh Sau Cheong; Wail Muin Ismail, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This investigation examines the influence of knowledge about learning difficulties (LD) on the teaching performance of general educators who teach students with LD in intermediate schools in Riyadh, the Kingdom of Saudi Arabia (KSA). It also aims to analyse the moderating effect of the amount of teaching experience in this relationship. A questionnaire survey was used to collect data from 401 general educators in regular intermediate schools in Riyadh. Those educators completed the questionnaire containing items related to knowledge of LD, and they also completed a teaching performance questionnaire. The data collected in this study were analysed using a structural equation modelling approach (SEM) via analysis of moment structures (AMOS). The findings from the structural analysis indicated that the general educators’ knowledge was significantly influenced by their performance. A moderation analysis confirmed the significant effect of years of teaching experience on the relationship between knowledge and teaching performance. Accordingly, the findings will contribute to the body of knowledge in the KSA regarding the knowledge of general educators and their practices. The findings will also be beneficial to educationists in the field of LD and policymakers in the Ministry of Education. This research also s has the potential to reflect positively on general educators’ teaching performance, thus enhancing their handling of students with LD.